Atmospheric iron particles in PM2.5 from a subway station, Beijing, China. (15th August 2022) - Zhang, Mengyuan; Shao, Longyi; Jones, Tim; Feng, Xiaolei; Ge, Shuoyi; Yang, Cheng-Xue; Cao, Yaxin; BéruBé, Kelly; Zhang, Daizhou
Abstract: Particulate matter pollution in the subway station's atmosphere can seriously influence the air quality and impacts on the health of subway workers and commuters. In this study, PM2.5 samples were collected from different locations within a subway station in Beijing, and the individual particles were analyzed for morphology and composition by Transmission Electron Microscopy with Energy Dispersive X-ray Spectrometry (TEM-EDX). The results showed that the concentration of PM2.5 in subway stations was affected by both indoor and outdoor sources. Particles generated by train-related sources such as resuspension, wheel, rail, brake and collector shoe abrasion were a significant source of airborne pollution in the subway atmosphere. Within the subway station PM2.5, Fe was the dominant element, and was detected in more than 75% of all particles analyzed. The Fe-rich particles were identified in railway carriages (79.4%), station concourse (65.3%), and platforms (61.3%). The geometric mean diameter of Fe-rich particles was 0.34 μm, which was smaller than that of all detected particles. Cr, Mn and other metals were often detected in the Fe-rich particles, reflecting metal alloys used in the wheels and tracks. A better understanding of the particle distribution around different areas of the subway system and the physicochemical characteristics of these Fe-rich particles is critical in developing a meaningful assessment of the risk posed by particles in the subway atmosphere. Highlights: The majority of PM2.5 in the subway's atmosphere are Fe-rich particles. Fe-rich particles are mainly derived from mechanical abrasion at the brake-wheel-rail interfaces. The Fe-rich particles typically exist as Fe–Mn alloy fragments.